PERAN PENYULUH PERTANIAN DALAM PENERAPAN TEKNOLOGI BUDIDAYA TOMAT (Lycopersicun esculentum L.) DI DESA LOLENG KECAMATAN KOTA BANGUN KABUPATEN KUTAI KARTANEGARA (The Role of Agricultural Extension in the Application of Cultivation Technology of Tomato (Lycopersicun esculentum L.) in Loleng Village Kota Bangun Subdistrict Kutai Kartanegara District) - NIKE WIDURI; MIDIANSYAH EFFENDI; HERSON HERSON (Universitas Mulawarman (University of Mulawarman), 2018)
This study aimed to know the role of agricultural extension in the development of tomato cultivation, the application level of tomato cultivation technology, and the relationship between the role of agricultural extension. The sampling method in this study was stratified random sampling. The data were analyzed by using Rank Spearman. The results showed that the role of agricultural extension in the technology of tomato cultivation was very important position with an average score of 39.16, the level of application of tomato cultivation technology was in a high position with an average score of 45.47, there is a close relationship between the role of agricultural extension with the application level of tomato cultivation technology.